2022
DOI: 10.1155/2022/7397872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coffee Husk Compost and NPSB Fertilizers on Selected Soil Chemical Properties of Potato Field in Chora District, South West Ethiopia

Abstract: Field experiment was conducted in Chora District of south western Ethiopia, to evaluate the effect of different rates of coffee husk compost (CHC) and 18.9N + 37.7P + 6.94S + 0.15B (NPSB) in the form of NH4, P2O5, SO4−, and B2O5, repectively, blended fertilizer on selected soil chemical properties of potato field during 2021. The treatment consisted of four rates of CHC (0, 2.5, 5, and 7.5 t ha−1) and four rates of blended NPSB fertilizer (0, 112.5, 150, and 187.5 kg ha−1). The experiment was laid out in rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Besides, integrated application of inorganic nutrients with organic nutrients improves soil chemical properties [17][18][19]. For instance, Jibril and Bekele [19] reported that the higher total nitrogen (26%), available phosphorus (3.57%), and sulfur (4.36%) were obtained from a combined application of 7.5 t of cofee husk compost and 112.5 kg of NPSB•ha −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, integrated application of inorganic nutrients with organic nutrients improves soil chemical properties [17][18][19]. For instance, Jibril and Bekele [19] reported that the higher total nitrogen (26%), available phosphorus (3.57%), and sulfur (4.36%) were obtained from a combined application of 7.5 t of cofee husk compost and 112.5 kg of NPSB•ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, integrated application of inorganic nutrients with organic nutrients improves soil chemical properties [17][18][19]. For instance, Jibril and Bekele [19] reported that the higher total nitrogen (26%), available phosphorus (3.57%), and sulfur (4.36%) were obtained from a combined application of 7.5 t of cofee husk compost and 112.5 kg of NPSB•ha −1 . Furthermore, Tana and Woldesenbet [18] recorded that the application of 5 t FYM•ha −1 along with 75% recommended rates of inorganic N and P (17.25 kg N•ha −1 and 34.5 kg P 2 O 5 ha −1 ) was found to be superior and increased soil organic carbon content by 36 and 44.6%, available phosphorus by 70.5 and 78.2%, and available potassium by 42.5 and 26.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Tis might be attributed by high amount of organic matter in BS, which enhances the OC content of the soil; organic materials have a major impact on mineralization rates by increasing soil organic carbon directly [68]. Other previous studies also demonstrated signifcantly increasing OC of the soil by the application of organic fertilizers compared to CF [69][70][71][72].…”
Section: Soil Chemical Propertiesmentioning
confidence: 96%
“…Tis could attribute to the higher CEC and organic matter content in BS and the nature of the organic matter to bufer change in pH. Previous studies reported increasing organic matter content and available nutrients with the application of organic fertilizers, which in turn increases the exchangeable bases and the cation exchange capacity of the soil [17,69,79]. Organic matter increases the bufering capacity of soils and prevents acidifcation through binding cations [80].…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%